2022
DOI: 10.1002/chem.202202029
|View full text |Cite
|
Sign up to set email alerts
|

σ‐Holes in Iodonium Ylides: Halogen‐Bond Activation of Carboxylic Acids, Phenols and Thiophenols May Enable Their X−H Insertion Reactions

Abstract: The first systematic evaluation of the electrostatic potential energy maps of iodonium ylides was conducted. We determined that they possess two σ‐holes of differing electron deficiencies, with the more electropositive σ‐hole located opposite the dative I−C bond to the β‐dicarbonyl motif, and the lesser electropositive σ‐hole located opposite the iodoarene C−I bond. We also conducted the first systematic evaluation of carboxylic acids, phenols and thiophenols in the O/S‐alkylation reaction of iodonium ylides. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Invoking charge assistance by placing a negative charge on the base can be an important amplification factor. [51][52][53][54][55][56][57][58][59] When the base was mutated to Cl À , this anion situated itself directly along the Ge-Cl axis of GeH 3 Cl with R(ClÁ Á ÁCl) = 3.223 Å, but with only a slightly negative interaction energy of À0.34 kcal mol À1 . AIM and NBO analysis point to a XB as the sole source of stability of this dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Invoking charge assistance by placing a negative charge on the base can be an important amplification factor. [51][52][53][54][55][56][57][58][59] When the base was mutated to Cl À , this anion situated itself directly along the Ge-Cl axis of GeH 3 Cl with R(ClÁ Á ÁCl) = 3.223 Å, but with only a slightly negative interaction energy of À0.34 kcal mol À1 . AIM and NBO analysis point to a XB as the sole source of stability of this dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, there were no quantitative evaluations of σ-holes in iodonium ylides [ 98 99 ], even though halogen bonding had been invoked for years when describing reactions of such ylides. In 2022, Murphy et al used computational analysis to assess iodonium ylides for their σ-holes, and found that two of these existed, with one situated opposite the arene and the other opposite the β-dicarbonyl motif ( Figure 4 ) [ 100 ]. In the dimethyl malonate-derived ylide I-10 , the σ-hole opposite the β-dicarbonyl was stronger with an electrostatic potential of 0.084 e , compared to the 0.049 e found for that opposite the arene.…”
Section: Reviewmentioning
confidence: 99%
“…In addition to Neiland’s disclosure of the reactions between iodonium ylides and hydrochloric acid ( Scheme 1 ) [ 1 , 102 ], others have also reported that both strong acids (e.g., TsOH, TFA, and trichloroacetic acid) and even weak acids (e.g., HF, Et 3 N·3HF, and AcOH) react with iodonium ylides to give formal X–H insertions [ 127 – 130 ]. In 2022, Murphy et al disclosed a computational and experimental investigation into the reaction scope and the mechanism by which such X–H insertion reactions could occur ( Scheme 10 ) [ 100 ]. Systematic evaluation of acidic compounds showed that carboxylic acids (p K a ≈ 5; 85–99% yield) and thiophenols (p K a ≈ 7; 50f , 59%) were especially viable, whereas electron-rich phenols (p K a ≈ 10; 50d , <15% yield) were not.…”
Section: Reviewmentioning
confidence: 99%
“…The necessity and generality of the κ 2 coordination of the dicarbonyl precursor (prior to PhI elimination) was probed by use of two additional ylides: 2,4-pentanedione-derived ( i.e. acac-derived) ylide 43 and dimedone-derived ylide. 44 Acac-derived ylide is expected to coordinate to the metal like the diester-derived ylide and therefore should exhibit similar reactivity.…”
mentioning
confidence: 99%